Expansion of supraglacial lake area, volume and extent on the Greenland ice sheet from 1985 to 2023 - Yubin Fan; Chang-Qing Ke; Lanhua Luo; Xiaoyi Shen; Stephen John Livingstone; James M. Lea (Journal of Glaciology)
Supraglacial lakes (SGLs) are widespread across the Greenland ice sheet and cause transient changes in ice flow. Here, we produce the first annual ice-sheet wide database of maximum summer SGL extents spanning 1985 to 2023 using all July and August Landsat images. Lake visibility percentages were calculated to estimate the uncertainty induced by variable image data coverage. SGLs were mainly distributed between 1000 and 1600 m elevation, with large lake area observed in northwestern, northeastern and southwestern basins. Lake area increased at a rate of 50.5 km2 a−1 across the entire Greenland, and lakes advanced to higher elevations at an average rate of 10.2 m a−1 during 1985–2023. We leveraged spatiotemporally matched ICESat-2 and Landsat 8 reflectance data to develop a deep learning model for lake depth inversion for the period 2014–23. This model demonstrates the highest accuracy among all image-based methods, albeit with an underestimation of ~15% when compared to ICESat-2 data. A significant positive correlation between lake volume and area is used to up-scale the approach to the entire time period, indicating a lake volume increase of 221.9 ± 63.6 × 106 m3 a−1. Increasing air/land surface temperature, surface pressure and decreasing snowfall were the most important contributing factors in driving lake variability.